1987
DOI: 10.1177/001698628703100302
|View full text |Cite
|
Sign up to set email alerts
|

Accelerative Strategies: How Effective are they for the Gifted?

Abstract: Accelerative strategies offer gifted students the opportunity to participate in educational programs suited to their particular needs and interests. Yet, fear of possible negative effects of acceleration prevents many educators from advocating these options. The Study of Mathematically Precocious Youth (SMPY) has evaluated the long-term effects of a variety of accelerative options for a group of highly gifted students. Academic achievements, extracurricular activities, goals and aspirations, and social and emo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
55
0
3

Year Published

1989
1989
2015
2015

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(61 citation statements)
references
References 9 publications
3
55
0
3
Order By: Relevance
“…Cunningham and Rinn (2007) found similar results with regard to the general and emotional self-concept, such that gifted adolescents experienced a significant increase in general and emotional self-concept scores over the course of a three-week summer program. Various other researchers have found similar increases in self-concept across a variety of selective programs and environments for the gifted (Brody and Benbow 1987;Kolloff and Moore 1989;Vaughn et al 1991). These studies suggest that even though a summer program or environment may be for academically gifted students, the effects on both academic and non-academic self-concepts are noteworthy.…”
Section: Social Comparison and Self-conceptsupporting
confidence: 54%
“…Cunningham and Rinn (2007) found similar results with regard to the general and emotional self-concept, such that gifted adolescents experienced a significant increase in general and emotional self-concept scores over the course of a three-week summer program. Various other researchers have found similar increases in self-concept across a variety of selective programs and environments for the gifted (Brody and Benbow 1987;Kolloff and Moore 1989;Vaughn et al 1991). These studies suggest that even though a summer program or environment may be for academically gifted students, the effects on both academic and non-academic self-concepts are noteworthy.…”
Section: Social Comparison and Self-conceptsupporting
confidence: 54%
“…In their study of the long-term effects of an enrichment program for gifted elementary school students, Moon et al found the long-term benefits of participating in a gifted program to be mostly positive, including an increased self-concept, increased motivation, an increase in basic thinking skills, and an increase in autonomous learning. Although Marsh et al (1995) did identify a group of 9-year-old students suffering a decline in academic self-concept after being accelerated into a gifted class (indeed a decline in nonacademic self-concepts as well), most studies of accelerated students do not find an consistent pattern of lowered self-concepts and prolonged negative motivational consequences (see Brody and Benbow 1987). In fact, long-term prospects based on research are quite positive (Lubinski 2004).…”
mentioning
confidence: 99%
“…From the perspective of criteria set in other international jurisdictions, Simbir fulfilled the conditions of acceleration (e.g., Brody & Benbow, 1987;Gross, 1992;Pollins, 1983, Stanley, 1978. First, Simbir had a total IQ of 137 in the WISC-111, when typically acceleration usually requires an IQ of 130 (Khaleefa, 2005).…”
Section: Early Elementary Years and Academic Accelerationmentioning
confidence: 99%
“…Acceleration, however, it is considered by the Sudanese Ministry of Education as gonha or of questionable significance (Omar, January, 2005). In fact, it is viewed with some skeptism and apprehension (Jarwan, 1998(Jarwan, , 2002, and at the present no legislation exists concerning acceleration whether it relates to early admission to kindergarten or school or to skipping different grades in school.From the perspective of criteria set in other international jurisdictions, Simbir fulfilled the conditions of acceleration (e.g., Brody & Benbow, 1987;Gross, 1992;Pollins, 1983, Stanley, 1978. First, Simbir had a total IQ of 137 in the WISC-111, when typically acceleration usually requires an IQ of 130 (Khaleefa, 2005).…”
mentioning
confidence: 99%